STRATEGI DALAM MENINGKATKAN OMZET PENJUALAN PADA TOKO DUO SISTER HIJAB KOTA BENGKULU - Annisa Murti; Sri Ekowati ((JEMS) Jurnal Entrepreneur dan Manajemen Sains, 2021)
Sister Duo Hijab store is a company engaged in fashion which produces and markets hijab, clothes, pants, hijab shirts, tuspins etc. This business has been running for 3 years and is growing well but has many competitors in the same field. This study is entitled "analysis of marketing strategies to increase sales in the city of Bengkulu hijab duo sister shop". This research is based on the importance of marketing strategies in an organization. This study also aims to determine the company's internal and external factors, determine the company's position and determine the right marketing strategy for the company to increase sales.